KEUNGGULAN PRODUK BERBASIS KOMPETENSI PENGETAHUAN PASAR DALAM MENINGKATKAN KINERJA PEMASARAN: (STUDI KASUS PADA KELOMPOK PENGRAJIN KRUPUK RAMBAK DESA PENANGGULAN, PEGANDON, KENDAL 2019) - Prasetyo, Ageng (PRIMA EKONOMIKA, 2020)
ABSTRACTThis study focus on how the company need to know about the market expectation before theproduct was launched esspecially in Kelompok Pengrajin Krupuk Rambak Desa Penanggulan,Pegandon, Kendal in 2019. The ability of the company to know the market was called themarket knowledge competence. Its concist of three major aspects such as customer knowledgecompetence, competitor knowledge competence and the interface between R&D with marketingdepartment. The higher market knowledge competence was predicted can creates the higher thecompetitive advantage in the market place. And as the result the competitive advantage canincrease the marketing performance, these was inluded sales volume, sales growth andcustomers growth. Populations of this study were 1000 customers of Kelompok PengrajinKrupuk Rambak Desa Penanggulan, Pegandon, Kendal, and the samples of this study were 100customers which devided into 2 categories of monthly purchases amount. We expected thisstudy could be applied in the company in order to support policies and strategies in themarketing field mainly on developing new products.Keywords : marketing knowledge competences, competitive advantages, marketingperformance.